A meta-analysis on the effects of incarceration-based opioid substitution treatment - Boksán, Klara; Dechant, Michael; Weiss, Maren; Hellwig, Almut; Stemmler, Mark (Medicine Science and the Law, 2022)
Opioid substitution treatment (OST) is a common treatment for individuals who use opioids; however, empirical evidence on the effects of OST during incarceration is scarce. Our aim was to conduct a meta-analysis on the effects of incarceration-based OST on substance use, treatment engagement post-release and re-incarceration. Method: We searched for studies on individuals who were incarcerated and treated with OST, compared to a comparison group. Studies were only included if they reported data post-release. Results: N = 15 studies met the inclusion criteria. We found less opioid use, less other drug use, higher treatment engagement post-release and less re-incarceration among treated individuals compared to the comparison group. Moderator analyses showed some influence of length of follow-up period and study quality. Conclusions: Incarceration-based OST reduces drug use, re-incarceration and leads to higher treatment engagement after release. More research is needed on the effects of incarceration-based OST n secondary outcomes (e.g. health and social integration) and on factors that moderate these effects.<br
CRIS-Team Scopus Importer:2022-08-19
Keywords: incarcerated populations; meta-analysis; opioid substitution treatment; Opioid use disorder; treatment of incarcerated individuals

Hardly any gender differences among opioid users in prison - Boksán, Klara; Weiss, M.; Geißelsöder, Kerstin; Dechant, Michael; Endres, J.; Breuer, M.; Stemmler, Mark; Wodarz, N. (Forensische Psychiatrie, Psychologie, Kriminologie, 2023)
Background A high proportion of incarcerated women exhibit opioid dependence. Concerning the question whether women and men differ in their opioid use and whether empirical evidence for a telescoping effect (later initiation of drug use with accelerated progression of dependence) in women can be found, the research situation is ambiguous. In this respect, there is a lack of studies on possible gender differences, particularly in the correctional setting.Objective In a sample of n = 247 opioid-dependent individuals incarcerated in Bavarian prisons we compared female (n = 31) and male (n = 216) study participants regarding age, drug use, substitution treatment, psychological preload, education, and economic situation.Method Data were collected during an initial interview in prison as part of the ongoing study "Incarceration and opioid dependence-an evaluation study ".Results There were no differences in drug use between the two gender groups; consequently, no evidence of a telescoping effect among opioid-dependent female prisoners was found. Furthermore, no differences between women and men regarding substitution treatment, education, and economic situation were found. Women were more likely to report having suffered from depression prior to incarceration and having experienced sexual abuse.Conclusion Evidence was found of greater psychological distress among female compared with male incarcerated persons with opioid dependence, but strikingly few differences beyond that. It seems conceivable that in this population a particularly severe course of opioid dependence could be present, which makes any gender-specific differences recede into the background.
CRIS-Team WoS Importer:2023-01-27

Opioid substitution treatment, relapse and addiction-related outcomes in prison setting and after release: A longitudinal study - Geißelsöder, Kerstin; Weiss, Maren; Boksán, Klara; Dechant, Michael; Endres, Johann; Breuer, Maike; Stemmler, Mark; Wodarz, Norbert (Nordic Studies on Alcohol and Drugs, 2024)
Aims: Opioid addiction is a common problem among prisoners. The aim of this study was to examine differences between people who are incarcerated receiving opioid substitution treatment (OST) and those not receiving OST on addiction-related outcome variables during incarceration and after release from prison. Variables covered illicit use of opioids, non-prescribed substitution medication and other substances, opioid withdrawal symptoms, opioid craving, non-fatal overdoses and post-release substitution treatment. Design: Interviews (European Addiction Severity Index, EuropASI) were conducted with 247 participants in German prisons before release. Participants were interviewed again 1 month and 3–6 months after release from prison. Results: During incarceration, participants who received OST used less illicit opioids and non-prescribed substitution medication than those who did not receive OST. After release from prison, participants in the OST group reported less illicit opioid use and less non-prescribed substitution medication use, as well as less opioid craving. Participants who received OST in prison were more likely to be in OST at post-release follow-up than those who had not received in-prison OST. Conclusion: OST appears to have a positive effect on illicit opioid use and craving both in prison and after release, as well as on treatment at follow-up, which can be considered a protective factor.
Created from Fastlane, Scopus look-up
Keywords: opioid addiction; opioid substitution treatment; prison